Anharmonic Vibrational Frequencies and Spectroscopic Constants for the Detection of Ethynol in Space - Dallas, Jax D.; Westbrook, Brent R.; Fortenberry, Ryan C. (Frontiers in Astronomy and Space Sciences, 2021)
The ethynol (HCCOH) molecule has recently been shown to be present in simulated astrochemical ices possibly linking it to molecular building blocks for interstellar complex organic molecules like amino acids. The proposed reaction mechanism suggests the simultaneous formation of both ketene and ethynol from mixed carbon monoxide/water ice in simulated interstellar conditions. Rigorous anharmonic spectral data within both the IR and microwave regions are needed for possible detection of ethynol in the interstellar medium. This study provides the first such data for this molecule from high-level quantum chemical computations where experiment is currently lacking. Ethynol has a B_eff comparable to, but distinct from acetonitrile at 9652.1 MH and three notable infrared features with two in the hydride stretching-regions and the C-C stretch at 2212.8 cm^-1. The ketene isomer has already been detected in the ISM, and the possible detection of ethynol made possible by this work may lead to a deeper understanding of the proposed ice formation mechanism involving both species and how this relates to the molecular origins of life.